External match-play loads in elite female assistant soccer officials - Carling, C.; Gruson, B.; Pavillon, T.; Leprince, C.; Thivilier, F.; Prat, J. M.; Doudet, F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In soccer, little research has examined the general physical demands of match-play in the contemporary elite female central referee [1] and to our knowledge, none exists in assistant referees (AR). Recent research [2] has shown that female central referees experience temporal deteriorations in physical performance across match-play. Once again however, no study has attempted to confirm whether similar declines occur in AR. This study aimed to 1) describe the overall external match loads in elite female AR during official matches, 2) compare performance across halves and whether decrements occur during the final 15-minute intervals of each match half.